PRE-FLOOD DISASTER MITIGATION BASED ON COMMUNITY EMERGENCY FOOD PROCESSING IN DORANG VILLAGE - Linda Nurul Amaliyah; Windy Windayanti; Dany Miftah M. Nur (International Journal of Multidisciplinary Reseach, 2025)
Floods have often occurred in Indonesia recently, causing a number of damages that require people to evacuate or live in emergency places for a while. One of them is in Dorang Village, not only damage to housing, natural disasters also cause damage to social infrastructure at the disaster site which hampers victims' access to sources of food needs. Food insecurity that occurs after a disaster can be overcome by processing emergency food which is expected to meet the nutritional needs of people in disaster-affected areas, especially during panic periods when public kitchens are not operating properly. The purpose of this study was to analyze pre-disaster flood mitigation based on emergency food processing in Dorang Village, Nalumsari, Jepara. Researchers used data collection methods of observation, interview, and documentation. The results of this study show that emergency food processing is an appropriate way of pre-flood disaster mitigation when infrastructure is hampered and an alternative way to meet food needs during a disaster.